Estimation of static modulus of carbonate formation for Rumaila oil field - Mahdi, Doaa Saleh; A.Alrazzaq, Ayad A.Alhaleem; Khan, Modhar (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Elastic parameters are essential for understanding the behavior of materials under stress, including their tendency for deformation and failure. Elastic modulus is a key parameter, which can be determined using static and dynamic methods. Dynamic methods involve analyzing properties from well logging such as density and wave velocity (compressional and shear waves), while static techniques quantify properties in a laboratory setting. While static techniques are the most accurate, they are also expensive and time consuming. However, there are correlations available to estimate static modules from dynamic modules, although many are specific to certain formations and not applicable to different rock types. In this paper, a new correlation was developed for predicting the static Young’s modulus for carbonate formations in the Rumaila Oil Field based on dynamic modulus. Data from 4803 points in an 8.5 in hole size section between 1980 m and 2711 m depth were collected. The results showed that the new correlation accurately predicted the static Young’s modulus of carbonate formation, a correlation coefficient (RSQ) of 97%, and an average absolute error of 8.15%. The new correlation provides a continuous profile of static Young’s modulus with depth and ultimately leads to reduce the cost of estimating elastic properties in carbonate formations in the Rumaila Oil Field.